Perceived social support as predictor of university adjustment, and academic achievement amongst first year undergraduates in a Malaysian public unversity - Abdullah, Maria Chong; Kong, Luo Lan; Talib, Abd Rahim (Universiti Utara Malaysia Press, 2014)
Purpose – This study was conducted to examine relationships between perceived social support, university adjustment and academic achievement of first semester students enrolled in various undergraduate programs in a Malaysian public university. Methodology – This study employed a quantitative approach with a descriptive correlation design to address the research objectives. The adapted version of the “Interpersonal Support Evaluation List” (1985) and the “Student Adaptation to College Questionnaire” (1999) were used to assess students’ perceived social support and university adjustment respectively. A total of 250 first year undergraduates were selected as respondents using cluster random sampling technique. Findings – Findings revealed a significant and positive relationship between students’ perceived social support and their overall university adjustment as well as all the four adjustment dimensions namely academic adjustment, social adjustment, personal-emotional adjustment, attachment to university, and academic achievement. Results also indicated that students’ overall university adjustment and academic achievement were significant and positively predicted by social support. Significance – This study provides important evidence for undergraduates, lecturers, university administrators, and the community at large regarding the important role of social support in university adjustment and academic performance. It is suggested that a university should provide support services to assist new undergraduates to overcome their adjustment problems.